Prevalence of Pelvic Floor Disorders in Parous Women from the Tibet Autonomous Region: A Cross-Sectional Study - Lv A; Ding T; DeQiong; DaWaZhuoMa; Cai L; Zhang Y; Yin J; SeZhen; Lv Q (Journal of Multidisciplinary Healthcare, 2024)
Aiming Lv,1,2 Tong Ding,2 DeQiong,2 DaWaZhuoMa,2 Long Cai,2 Yutong Zhang,2 Jinyu Yin,2 SeZhen,2 Qiubo Lv1 1Department of Obstetrics and Gynecology, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People’s Republic of China; 2Women and Children’s Hospital of Tibet Autonomous Region, Lhasa, Tibet Autonomous Region, People’s Republic of ChinaCorrespondence: Qiubo Lv, Department of Obstetrics and Gynecology, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, No. 1 DaHua Road, Dong Dan, Beijing, 100730, People’s Republic of China, Tel +86 13801192185, Fax +86 10 85136220, Email lvqiubo@yeah.netPurpose: Pelvic floor disorder (PFD) seriously affects the everyday life of women. This cross-sectional study aimed to evaluate the prevalence and risk factors for postpartum PFD in women living in the Tibet Autonomous Region (TAR).Methods: Parous women who attended the outpatient gynaecology clinic at our hospital between June 2022 and August 2022 were screened in this study. The demographic and clinical data of these women were collected. Their pelvic floor functions were evaluated via a pelvic organ prolapse (POP) quantification examination, the Pelvic Floor Distress Inventory Questionnaire-20 (PFDI-20) and the Overactive Bladder Symptom Score (OABSS).Results: A total of 201 women were included in this study, of whom 81.09% (163/201) were Tibetan. Twenty-seven women (13.43%) were diagnosed with POP stage ≥ 2 and 27 women (13.43%) with an OABSS score ≥ 3. The median PFDI-20 total score was 4.17 (range 0– 43.75). Han women (n = 38) in the TAR had much lower PFDI-20 total scores, compared with Tibetan women (n = 163) (p < 0.05). The results of the multiple linear regression models showed that the PFDI-20 scores obtained from women living in the TAR were closely related to parity, history of heavy weight lifting, age, history of instrumental deliveries, ethnicity and number of caesarean sections.Conclusion: Pelvic floor disorder is common among parous women living in the TAR. Ethnicity, parity, history of heavy weight lifting, age, history of instrumental deliveries and number of caesarean sections are the factors closely related to the PFDI-20 scores.Keywords: pelvic floor disorder, Tibet Autonomous Region, pelvic organ prolapse, urinary incontinence, overactive bladder symptoms